The Oneida Community and the utility of liberal capitalism. (21st November 2019) - Coffee, Kevin
Abstract : Historians studying the utopian Oneida Community have often located its demise in rising internal dissent and failing consensus among its members, with special emphasis on the personal jealousies and generational tensions that its practice of group marriage may have produced. Those studies step past the essential place of work and industry in communal life and especially the community's theology, which equated economic prosperity with Christian virtue. This essay reframes our understanding of the political economy of the Oneida Community, with specific attention to their last decade, and the social tensions stoked by their reliance upon market capitalism and waged labour. While acknowledging the internal dissent that accompanied the structural demise of the commune, the present study asks how such discord arose from business-centred theology within the social environment of competition and a prolonged economic depression. The Community's dependence upon the surrounding capitalist economy challenged their self-described 'Bible communism' and precipitated its demise.